A method for preparing lithium-doped modified trimanganese tetraoxide by using lithium-doped lithium iron manganese phosphate

CN118108258BActive Publication Date: 2026-11-03HUNAN BRUNP RECYCLING TECH CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410273354.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2026-11-03
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

In existing technologies, when extracting metal salts from spent lithium iron phosphate batteries, manganese is treated as an impurity element through co-precipitation, resulting in low losses and economic efficiency. Furthermore, the preparation process is energy-intensive and fails to effectively utilize the lithium manganese liquid.

Method used

By synergistic leaching of lithium manganese with organic acids and strong oxides, and through selective leaching and oxidation precipitation reactions, combined with surfactants to regulate particle morphology, pre-doped modified manganese tetroxide was prepared, achieving lithium doping and coating and spherical particle growth, and reducing agglomeration.

Benefits of technology

This method improves the high-value utilization of lithium manganese liquid, reduces energy consumption, enhances the purity and activity of the prepared manganese tetroxide, making it suitable for lithium manganese oxide battery materials, simplifies the regeneration process of phosphorus iron slag, and improves the utilization rate of lithium salts and the electrochemical performance of lithium manganese oxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118108258B_ABST
    Figure CN118108258B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing pre-doped lithium modified trimanganese tetraoxide from lithium manganese iron phosphate, and relates to the field of battery recycling. The method comprises the following steps: dissolving lithium manganese iron phosphate battery material in a mixed solution of organic acid and strong oxidant, adding ammonia and manganese salt into the obtained lithium-rich manganese liquid for metal concentration regulation; then, adding a surfactant and an oxide for oxidation precipitation reaction to obtain pre-doped lithium surface modified trimanganese tetraoxide. The application uses organic acid and strong oxidant to selectively leach manganese and lithium from lithium manganese iron phosphate. In the oxidation precipitation process, the precipitation is nucleated. The adsorption of Mn to Li is used to realize lithium doping coating. The addition of a surfactant regulates the growth of particles into spherical particles, reduces agglomeration, and the obtained pre-doped lithium surface modified trimanganese tetraoxide can be used for preparing lithium manganate material, that is, the short-flow selective leaching of waste lithium manganese iron phosphate is realized, and the leached lithium-containing manganese liquid can be used for high-value utilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery recycling, and in particular to a method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate. Background Technology

[0002] With the rapid development of new energy vehicles, lithium battery production has accelerated. In particular, lithium iron phosphate power batteries are widely used due to their good safety performance and long cycle life. Meanwhile, manganese iron phosphate is gradually being valued and entering the battery market due to its high energy density. Its properties are similar to those of lithium iron phosphate and lithium manganese phosphate, and it has better thermal stability, chemical stability and economy than ternary materials.

[0003] With the increasing application of lithium manganese iron phosphate (LFP) batteries, the disposal of spent LFP batteries needs to be considered in advance. Current technologies for extracting various metal salts from spent LFP batteries involve acid leaching to form a metal solution and preparing iron phosphate and lithium carbonate. In this method, manganese, as an impurity element, is transferred to the solid slag through a co-precipitation process, resulting in direct loss and ineffective utilization. Another method involves leaching lithium from the positive electrode material of LFP batteries and filtering to obtain a lithium-rich solution and manganese iron slag. The manganese iron slag is a mixture of manganese oxide and iron phosphate. The manganese iron slag is then calcined with sodium hydroxide, dissolved in water, and filtered to obtain a sodium manganate solution and iron phosphate. The sodium manganate solution is then subjected to a redox reaction with a reducing agent to obtain manganese dioxide. This method has high energy consumption and low economic viability for manganese byproducts.

[0004] Therefore, there is a need to develop a method for recovering lithium manganese iron phosphate with mild reaction conditions, less use of acids and alkalis, high economic efficiency of the recovered products, and low energy consumption. Summary of the Invention

[0005] This invention provides a method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate. By selectively leaching manganese lithium from lithium manganese iron phosphate and performing oxidation precipitation treatment, pre-lithium-doped surface-modified manganese tetroxide is obtained. This method can achieve short-process selective leaching of waste lithium manganese iron phosphate and also enable high-value utilization of the leached lithium-manganese-containing solution.

[0006] To address the aforementioned technical problems, one objective of this invention is to provide a method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate, comprising the following steps:

[0007] (1) Dissolve the lithium iron phosphate battery material in a mixed aqueous solution containing organic acid or organic acid salt and strong oxide, and filter after leaching reaction to obtain lithium-rich manganese liquid and iron phosphate slag.

[0008] (2) Add ammonia and manganese salt to the lithium-rich manganese solution to regulate the metal concentration;

[0009] (3) Add surfactant and oxide to the regulated solution to carry out oxidation precipitation reaction, and obtain pre-lithium-doped surface-modified manganese tetroxide after filtration and washing.

[0010] By adopting the above scheme, this application uses organic acids and strong oxides in a synergistic process to selectively leach manganese lithium metal from lithium iron phosphate. Iron is essentially not leached. If too much iron is leached, it will precipitate along with manganese during the oxidation precipitation process. Due to the significant difference in precipitation coefficients between iron and manganese, uneven co-precipitates will form, affecting the morphology and purity of manganese tetroxide and thus impacting product applications. During the oxidation precipitation reaction, ammonia can coordinate with the metal, regulating the metal precipitation process and controlling the morphology of the precipitate particles. If the ammonia concentration is too low, the morphology cannot form a near-spherical shape; if it is too high, too much metal will coordinate, causing metal residue in the mother liquor that cannot precipitate. During the growth of manganese trioxide (Mn), the adsorption of Li by Mn enables lithium doping and coating, increasing the in-situ lithium doping content of Mn tetroxide. This allows for a reduction in the amount of lithium salt used when it is subsequently used as a precursor for lithium manganese oxide and co-sintered with lithium salts to prepare lithium manganese oxide materials. During the oxidation precipitation reaction, precipitate particles tend to aggregate due to van der Waals forces. Adding surfactants reduces the interparticle forces, regulates particle growth to a spherical shape, and prevents powder agglomeration. Furthermore, during oxidation, the oxide or surfactant decomposes on the powder surface to generate bubbling micro-nuclei. Surfactants with oxidation functional groups can also oxidize Mn in situ. 2+ Mn 3+ The Mn3O4 generated during the co-precipitation process enhances the activity of subsequent manganese tetroxide particles as lithium manganese oxide materials.

[0011] As a preferred embodiment, in step (1), the organic acid is at least one of oxalic acid, citric acid, acetic acid, maleic acid, tartaric acid, benzoic acid, oxalic acid, malonic acid, succinic acid, phenylacetic acid, phthalic acid, and terephthalic acid.

[0012] As a preferred embodiment, in step (1), the organic acid salt is at least one of the organometallic salts of oxalic acid, citric acid, acetic acid, maleic acid, tartaric acid, benzoic acid, oxalic acid, malonic acid, succinic acid, phenylacetic acid, phthalic acid, and terephthalic acid.

[0013] As a preferred embodiment, in step (1), the strong oxide is persulfate, ozone, oxygen, sodium hypochlorite, hydrogen peroxide, or chlorine.

[0014] As a preferred embodiment, in step (1), the molar ratio of the organic acid or organic acid salt to the strong oxide is (0.4-0.8):1.

[0015] As a preferred embodiment, in step (1), the molar ratio of the strong oxide to lithium manganese iron phosphate in the lithium manganese iron phosphate battery material is (0.5-1.2):1.

[0016] As a preferred option, in step (1), the leaching reaction temperature is 60-90℃.

[0017] As a preferred option, in step (1), the leaching reaction time is 4-10 hours.

[0018] As a preferred embodiment, in step (1), the stirring rate of the leaching reaction is 200-450 rpm.

[0019] As a preferred embodiment, in step (1), the solid-liquid ratio in the leaching reaction is 4-12 mL / g.

[0020] As a preferred embodiment, in step (1), the lithium manganese iron phosphate battery material is waste lithium manganese iron phosphate cathode powder, waste lithium manganese iron phosphate battery powder, or waste lithium manganese iron phosphate electrode powder.

[0021] As a preferred embodiment, in step (2), the ammonia is at least one of ammonia water, ammonium chloride, ammonium sulfate, sodium 4-hydroxybenzenesulfonate, hydroxyacetamide, N-benzoyl-N-phenylhydroxylamine, ethylenediamine, and triethylamine.

[0022] As a preferred embodiment, in step (2), the manganese salt is at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, manganese acetate, and manganese phosphate.

[0023] As a preferred option, in step (2), the concentration of Mn metal in the solution after adjustment is 0.2-2.2 mol / L.

[0024] As a preferred embodiment, in step (2), the amount of ammonia added is 3-12% of the molar amount of Mn metal.

[0025] As a preferred embodiment, in step (3), the surfactant is at least one of pyrrolidone, polyvinylpyrrolidone, 1-vinyl-2-pyrrolidone, 5-methyl-2-pyrrolidone, 2-pyrrolidone-5-carboxylic acid, sodium 4-hydroxybenzenesulfonate, sodium 3-carboxybenzenesulfonate, sodium 3-aminobenzenesulfonate, sodium 4-vinylbenzenesulfonate, sodium 4-ethylbenzenesulfonate, sodium ligninsulfonate, sodium aminosulfonate, and sodium benzoyl thioethanesulfonate.

[0026] As a preferred embodiment, in step (2), the oxide is air, ozone, oxygen, persulfate, chlorine or sodium hypochlorite.

[0027] As a preferred embodiment, in step (2), the molar ratio of the surfactant to the Mn metal in the solution is (0.005-0.05):1.

[0028] As a preferred embodiment, in step (2), the molar ratio of the oxide to the Mn metal in the solution is (0.7-1.1):1.

[0029] As a preferred option, in step (2), the oxidation precipitation reaction temperature is 70-95℃.

[0030] As a preferred embodiment, in step (2), the stirring speed of the oxidation precipitation reaction is 300-500 rpm.

[0031] As a preferred option, in step (2), the pH value of the oxidation precipitation reaction is 8-10.

[0032] As a preferred option, in step (2), the oxidation precipitation reaction time is 10-20 h.

[0033] As a preferred embodiment, in step (1), the phosphate slag is dissolved in 1-3 mol / L sulfuric acid with a solid-liquid ratio of 3-8 mL / g. After filtration, phosphate seed crystals with an iron ion concentration of 10-25% molar ratio are added to the solution, resulting in a seed crystal concentration of 50-80 g / L and a D50 of 0.1-2.4 μm. The solution is aged for 4-10 h, filtered, washed, and dried, and then calcined at 500-800 °C to obtain battery-grade phosphate.

[0034] By adopting the above scheme, the regeneration treatment of the phosphate slag of this application can be achieved by directly adding seed crystals for precipitation after acid dissolution filtration and concentration adjustment, thus obtaining battery-grade phosphate slag. The regeneration process is simple, and impurity metal ions do not precipitate during the precipitation process.

[0035] To address the aforementioned technical problems, a second objective of this invention is to provide a method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate.

[0036] As a preferred embodiment, the pre-lithium-doped modified manganese tetroxide contains 68-75 wt% Mn, 0.8-1.8 wt% Li and 0.4-3.2 wt% C, and has a D50 of 10-15 μm.

[0037] As a preferred embodiment, the Fe content of the pre-lithium-doped modified manganese tetroxide is below 0.5 wt%.

[0038] To address the aforementioned technical problems, a third objective of this invention is to provide a lithium manganese oxide battery material, which is prepared by pre-doping lithium-modified manganese tetroxide.

[0039] As a preferred embodiment, the lithium manganese oxide battery material also includes lithium salt.

[0040] As a preferred embodiment, the pre-lithium-doped modified manganese tetroxide is mixed evenly with lithium salt, and then sintered at 600-800℃ to form a lithium manganese oxide battery material.

[0041] As a preferred embodiment, the lithium source is lithium hydroxide or lithium carbonate.

[0042] As a preferred embodiment, the molar ratio of the pre-lithium-doped modified manganese tetroxide to the lithium salt is 2:(1-2).

[0043] Compared with the prior art, the embodiments of the present invention have the following beneficial effects:

[0044] 1. This application uses organic acids and strong oxides in synergy to selectively leach manganese and lithium metal from lithium iron phosphate. Iron elements are basically not leached from the lithium-rich manganese solution. During the oxidation and precipitation process, the oxidant or surfactant decomposes on the powder surface, generating foaming precipitate nucleation centers. During the reaction, the precipitate particles tend to aggregate due to van der Waals forces. Adding surfactants reduces the forces between powder particles, controls the particle growth process to be spherical, avoids the agglomeration of the prepared pre-lithium-doped modified manganese tetroxide powder, and improves the morphology.

[0045] 2. During the oxidation precipitation reaction, surfactants with oxidizing functional groups can also oxidize Mn in situ. 2+ Mn 3+ The Mn3O4 generated during the co-precipitation process increases the activity of the manganese tetroxide particles prepared in this application as a precursor material for lithium manganese oxide. Due to the adsorption effect of Mn on phosphate and Li, lithium doping and coating can be achieved, increasing the in-situ lithium doping amount of the manganese tetroxide precursor. When preparing lithium manganese oxide material by blending and sintering with lithium salt, the amount of lithium salt can be reduced. At the same time, the repulsion between lithium salt and the surface of manganese tetroxide particles during sintering can be reduced, resulting in more uniform particle mixing and higher lithium salt utilization. In addition, an in-situ carbon coating layer can be formed on the surface after sintering, enhancing the conductivity of lithium manganese oxide. The gas generated by the decomposition of surfactant during sintering can slow down particle agglomeration, maintain the Li transport channel appropriately, and improve the reversible cycle stability of lithium manganese oxide material.

[0046] 3. The regeneration treatment of the phosphate slag in this application can be achieved by directly adding seed crystals after acid dissolution filtration and concentration adjustment to obtain battery-grade phosphate slag. The regeneration process is simple, and impurity metal ions do not precipitate during the precipitation process.

[0047] 4. This application is applicable to the recycling and reprocessing of various waste lithium manganese iron phosphate powders, used to prepare pre-doped lithium-modified manganese tetroxide, to achieve short-process selective leaching of waste lithium manganese iron phosphate, and to make high-value utilization of the leached lithium-containing manganese liquid. Attached Figure Description

[0048] Figure 1 This is a schematic diagram of the self-assembly and aggregation process of pre-lithium-doped modified manganese tetroxide in an embodiment of the present invention.

[0049] Figure 2 This application provides a schematic flowchart of a method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate.

[0050] Figure 3 SEM image of the pre-lithium-doped modified manganese tetroxide prepared in Example 1 of this application;

[0051] Figure 4 SEM image of the pre-lithium-doped modified manganese tetroxide prepared in Example 2 of this application;

[0052] Figure 5 SEM image of the pre-lithium-doped modified manganese tetroxide prepared in Example 3 of this application;

[0053] Figure 6 SEM image of the pre-lithium-doped modified manganese tetroxide prepared in Comparative Example 1 of this application;

[0054] Figure 7 SEM image of pre-lithium-doped modified manganese tetroxide prepared in Comparative Example 2 of this application. Detailed Implementation

[0055] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0056] Example 1

[0057] A method for preparing lithium-doped modified manganese tetroxide from lithium manganese iron phosphate, such as... Figure 2 As shown, it includes the following steps:

[0058] (1) Dissolve the waste lithium manganese iron phosphate battery cathode material in a mixed aqueous solution of citric acid and sodium persulfate oxidant with a molar ratio of 0.4:1, the molar ratio of sodium persulfate to lithium manganese iron phosphate is 0.5:1, the solid-liquid ratio is 4mL / g, the leaching reaction conditions are temperature 60℃, time 4h, stirring speed 200rpm, and after leaching reaction, filter to obtain lithium-rich manganese liquid and phosphorus iron slag.

[0059] (2) Add manganese sulfate to the lithium-rich manganese solution to adjust the metal concentration. After adjustment, the Mn metal concentration in the solution is 0.2 mol / L. At the same time, add ammonia water, and the amount of ammonia added is 3% of the molar amount of Mn metal.

[0060] (3) Add sodium 4-hydroxybenzenesulfonate surfactant and ozone to the regulated metal liquid for oxidation precipitation reaction. The reaction conditions are: temperature 70℃, stirring speed 300rpm, reaction pH 8, reaction time 10h, the molar ratio of sodium 4-hydroxybenzenesulfonate to Mn metal in the solution is 0.005:1, the molar ratio of ozone to Mn metal in the solution is 0.7:1, and after filtration and washing, pre-lithium-doped surface-modified manganese tetroxide is obtained.

[0061] (4) The phosphate slag obtained in step (1) was dissolved in 2 mol / L sulfuric acid with a solid-liquid ratio of 5 mL / g. After filtration, phosphate seed crystals with an iron ion concentration of 20% were added to the solution. After addition, the seed crystal concentration was 60 g / L and the D50 was 2.4 μm. After aging for 5 h, the solution was filtered, washed and dried, and then calcined at 650 °C to obtain battery-grade phosphate.

[0062] The prepared pre-lithium-doped surface-modified manganese tetroxide had the following elemental composition: 68% manganese by mass, 0.8% lithium by mass, 0.4% carbon by mass, and 0.08% iron by mass, with a compaction density of 1.8 g / cm³. -3 The D50 is 15um.

[0063] The battery-grade iron phosphate obtained was analyzed by ICP testing, and its composition content was found to be: Fe 3+ =31.0%, Mg 2+ =28ppm, Na + =71ppm, K + =80ppm, Cu 2+ =4ppm, Cr 3+ =10ppm, Pb 2+ =12ppm, iron-phosphorus ratio =0.98.

[0064] Example 2

[0065] A method for preparing lithium-doped modified manganese tetroxide from lithium manganese iron phosphate, such as... Figure 2 As shown, it includes the following steps:

[0066] (1) The positive electrode material of lithium manganese iron phosphate battery was dissolved in a mixed aqueous solution of phenylacetic acid and sodium hypochlorite with a molar ratio of 0.6:1, the molar ratio of sodium hypochlorite to lithium manganese iron phosphate was 0.8:1, the solid-liquid ratio was 8mL / g, the leaching reaction conditions were 70℃, 8h, and 300rpm. After the reaction, the lithium-rich manganese solution and phosphorus iron slag were obtained by filtration.

[0067] (2) Add manganese oxalate to lithium-rich manganese solution to adjust the metal concentration. After adjustment, the Mn metal concentration in the solution is 1.5 mol / L. At the same time, add hydroxyacetamide and the amount of ammonia added is 7% of the molar amount of Mn metal.

[0068] (3) Add sodium aminosulfonate surfactant and persulfate to the regulated metal liquid for oxidation precipitation. The reaction conditions are: temperature 80℃, stirring speed 400rpm, reaction pH 9, reaction time 15h, sodium aminosulfonate to Mn metal in solution molar ratio 0.025:1, persulfate to Mn metal in solution molar ratio 0.8:1. After filtration and washing, pre-lithium-doped surface-modified manganese tetroxide is obtained.

[0069] The elemental composition of the pre-lithium-doped surface-modified manganese tetroxide obtained was: manganese content 72% by mass, lithium content 1.4% by mass, carbon content 1.7% by mass, and iron content 0.21% by mass; the compacted density was 2.3 g / cm³. -3 The D50 value is 12 μm.

[0070] Example 3

[0071] A method for preparing lithium-doped modified manganese tetroxide from lithium manganese iron phosphate, such as... Figure 2 As shown, it includes the following steps:

[0072] (1) The positive electrode material of lithium manganese iron phosphate battery was dissolved in a mixed aqueous solution of malonic acid and sodium persulfate with a molar ratio of 0.8:1, the molar ratio of sodium persulfate to lithium manganese iron phosphate was 1.2:1, the solid-liquid ratio was 12mL / g, and the leaching reaction conditions were 90℃, 10h, and 450rpm. After the reaction, the lithium-rich manganese solution and phosphorus iron slag were obtained by filtration.

[0073] (2) Manganese sulfate was added to the lithium-rich manganese solution to adjust the metal concentration. After adjustment, the Mn metal concentration in the solution was 2.2 mol / L. At the same time, N-benzoyl-N-phenylhydroxylamine was added; ammonia was added at 12% of the molar amount of Mn metal.

[0074] (3) Add sodium benzoyl thioethane sulfonate surfactant and persulfate to the regulated metal liquid for oxidation precipitation. The reaction conditions are: temperature 95℃, stirring speed 500rpm, reaction pH 10, reaction time 20h, sodium benzoyl thioethane sulfonate to Mn metal molar ratio of 0.05:1, persulfate to Mn metal molar ratio of 1.1:1. After filtration and washing, pre-lithium-doped surface-modified manganese tetroxide is obtained.

[0075] The prepared pre-lithium-doped surface-modified manganese tetroxide had the following elemental composition: 75% manganese by mass, 1.8% lithium by mass, 3.2% carbon by mass, and 0.15% iron by mass; its compacted density was 2.9 g / cm³. -3 D50 is 10um.

[0076] Comparative Example 1

[0077] A method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate includes the following steps:

[0078] (1) Dissolve the waste lithium manganese iron phosphate battery cathode material in an aqueous solution containing sodium persulfate oxidant. The molar ratio of sodium persulfate to lithium manganese iron phosphate is 0.5:1, the solid-liquid ratio is 4mL / g, and the leaching reaction conditions are 60℃, 4h, and 200rpm. After the reaction, filter to obtain lithium-rich manganese liquid and phosphorus iron slag.

[0079] (2) Add manganese sulfate to the lithium-rich manganese solution to adjust the metal concentration. After adjustment, the Mn metal concentration in the solution is 0.2 mol / L. At the same time, add ammonia water, and the amount of ammonia added is 3% of the molar amount of Mn metal.

[0080] (3) Add sodium 4-hydroxybenzenesulfonate surfactant and ozone to the regulated metal liquid for oxidation precipitation reaction. The reaction conditions are: temperature 70℃, stirring speed 300rpm, reaction pH 8, reaction time 10h, the molar ratio of sodium 4-hydroxybenzenesulfonate to Mn metal in the solution is 0.005:1, the molar ratio of ozone to Mn metal in the solution is 0.7:1. After filtration and washing, pre-lithium-doped surface-modified manganese tetroxide is obtained.

[0081] The prepared pre-lithium-doped surface-modified manganese tetroxide had the following elemental composition: manganese 65% by mass, lithium 1.2% by mass, carbon 2.8% by mass, and iron 4.5% by mass; its compacted density was 2.3 g / cm³. -3 The D50 is 12.5um.

[0082] Comparative Example 2

[0083] A method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate includes the following steps:

[0084] (1) Dissolve the waste lithium manganese iron phosphate battery cathode material in a mixed aqueous solution of citric acid and sodium persulfate oxidant with a molar ratio of 0.4:1, the molar ratio of sodium persulfate to lithium manganese iron phosphate is 0.5:1, the solid-liquid ratio is 4mL / g, and the leaching reaction conditions are 60℃ temperature, 4h time and 200rpm stirring speed. After the reaction, filter to obtain lithium-rich manganese liquid and phosphorus iron slag.

[0085] (2) Add manganese sulfate to the lithium-rich manganese solution to adjust the metal concentration. After adjustment, the Mn metal concentration in the solution is 0.2 mol / L. At the same time, add ammonia water, and the amount of ammonia added is 3% of the molar amount of Mn metal.

[0086] (3) Ozone was added to the regulated metal liquid to carry out an oxidation precipitation reaction. The reaction conditions were: temperature 70℃, stirring speed 300rpm, reaction pH 8, reaction time 10h, ozone to Mn metal in solution molar ratio 0.7:1, and pre-lithium-doped surface-modified manganese tetroxide was obtained after filtration and washing.

[0087] The prepared pre-lithium-doped surface-modified manganese tetroxide had the following elemental composition: 78% manganese by mass, 0.1% lithium by mass, 0% carbon by mass, and 0.11% iron by mass; its compacted density was 1.2 g / cm³. -3 The D50 value is 28 μm.

[0088] Comparative Example 3

[0089] A method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate includes the following steps:

[0090] (1) Dissolve the waste lithium manganese iron phosphate battery cathode material in an aqueous solution containing citric acid. The molar ratio of citric acid to lithium manganese iron phosphate is 0.2:1, the solid-liquid ratio is 4mL / g, and the leaching reaction conditions are 60℃, 4h, and 200rpm. After the reaction, filter to obtain lithium-rich manganese liquid and phosphorus iron slag.

[0091] (2) Add manganese sulfate to the lithium-rich manganese solution to adjust the metal concentration. After adjustment, the Mn metal concentration in the solution is 0.2 mol / L. At the same time, add ammonia water, and the amount of ammonia added is 3% of the molar amount of Mn metal.

[0092] (3) Add sodium 4-hydroxybenzenesulfonate surfactant and ozone to the regulated metal liquid for oxidation precipitation reaction. The reaction conditions are: temperature 70℃, stirring speed 300rpm, reaction pH 8, reaction time 10h, the molar ratio of sodium 4-hydroxybenzenesulfonate to Mn metal in the solution is 0.005:1, the molar ratio of ozone to Mn metal in the solution is 0.7:1. After filtration and washing, pre-lithium-doped surface-modified manganese tetroxide is obtained.

[0093] The prepared pre-lithium-doped surface-modified manganese tetroxide had the following elemental composition: manganese 71% by mass, lithium 1.4% by mass, carbon 2.4% by mass, and iron 4.8% by mass; its compacted density was 2.4 g / cm³. -3 The D50 is 14.2 μm.

[0094] Application Example 1-3 and Comparative Application Example 1-3

[0095] A lithium manganese oxide battery material, the preparation method of which includes the following steps:

[0096] Using the pre-lithium-doped surface-modified manganese tetroxide from Examples 1-3 and Comparative Examples 1-3 as manganese sources, the manganese source was mixed with lithium carbonate at a molar ratio of 2:1.05, calcined in air at 800°C for 15 hours, then cooled to room temperature, and obtained by grinding and passing through a 300-mesh sieve.

[0097] Testing and Experiment

[0098] 1. Detect and calculate the leaching rate of different metals in the lithium-rich manganese solution of the example and comparative example. For example, the leaching rate of Li is calculated as follows: Li leaching rate = mass concentration of Li in the lithium-rich manganese solution in step (1) * solution volume / (mass content of Li in the positive electrode material of waste manganese iron lithium battery) × 100%. The calculation results are shown in Table 1 below.

[0099] Table 1 - Metal leaching rate in lithium-rich manganese solution in step (1) of Examples 1-3 and Comparative Examples 1-3 of this application.

[0100] Testing items Li leaching rate Mn leaching rate Fe leaching rate Example 1 98wt% 96wt% 0.5wt% Example 2 96wt% 94wt% 1.4wt% Example 3 97wt% 95wt% 0.7wt% Comparative Example 1 84wt% 65wt% 24wt% Comparative Example 2 98wt% 96wt% 0.5wt% Comparative Example 3 78wt% 60wt% 29wt%

[0101] As shown in Table 1, in Examples 1-3 of this application, citric acid and sodium persulfate were used in combination to selectively leach manganese lithium from waste lithium iron phosphate battery cathode materials. This can improve the leaching rate of Li and Mn metals in the lithium-rich manganese solution, while Fe is basically not leached. However, in Comparative Example 1, citric acid was not added during the leaching process of the waste lithium iron phosphate battery cathode materials, and in Comparative Example 3, sodium persulfate was not added during the leaching process of the waste lithium iron phosphate battery cathode materials. Due to the different redox potential of the solution compared with Example 1, the leaching rate of Li metal was low, and the leaching rate of Fe was high, which affected the morphology and purity of the pre-doped lithium-modified manganese tetroxide.

[0102] 2. The pre-lithium-doped surface-modified manganese tetroxide prepared in Examples 1-3 and Comparative Examples 1-2 were examined by scanning electron microscopy (SEM). The results are as follows: Figure 3-6 As shown, in step (3) of Examples 1-3 of this application, during the oxidation precipitation process, the precipitate particles tend to aggregate due to van der Waals forces during formation. Adding surfactants reduces the forces between powder particles, regulates the particle growth process to a spherical shape, and avoids powder agglomeration. Figure 3 Compared to Examples 2-3, the spherical morphology of Example 1 is the best, with uniform particles, regular surface structure, and less agglomeration. In contrast, in Comparative Example 1, due to the high leaching rate of Fe in the lithium-rich manganese solution, the large difference in the precipitation coefficients of iron and manganese led to the formation of uneven co-precipitates during the oxidation precipitation of manganese tetroxide, affecting the morphology and purity of manganese tetroxide. In Comparative Example 2, since no surfactant was added during the oxidation precipitation process, the precipitated particles had irregular shapes, poor sphericity, and were prone to agglomeration.

[0103] 3. The lithium manganese oxide battery material samples from the application examples and comparative application examples were mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 90:4:6. The mixture was prepared using N-methylpyrrolidone as a solvent, coated onto a 16μm thick current collector aluminum foil, dried at 120℃ for 20h, punched, and pressed to form a positive electrode sheet (containing 10mg of active material) with a diameter of 14mm and a thickness of 5μm. Using lithium metal as the negative electrode and 1mol / L LiPF6 / EC+DMC (volume ratio 1:1, battery grade) as the electrolyte, CR2032 coin cells were assembled. The cells were charged at a constant current of 1.0C to 4.35V, then switched to constant voltage charging to a current of 0.1C, and finally discharged at a constant current of 1.0C to 3.00V. The reversible capacity, 200-cycle capacity, and retention rate of the lithium manganese oxide battery material were tested. The test results are shown in Table 2 below.

[0104] Table 2 - Electrical performance test results of lithium manganese oxide materials prepared in the application examples and comparative application examples of this application

[0105]

[0106] As shown in Table 2, the lithium manganese oxide battery material prepared by sintering pre-lithium-doped modified manganese tetroxide with lithium salt in Example 1 exhibits high reversible capacity and cycle capacity retention rate after verification of its electrical performance, indicating that the prepared lithium manganese oxide battery material has high reversible cycle stability. In contrast, the lithium manganese oxide battery materials prepared by pre-lithium-doped modified manganese tetroxide in Comparative Examples 1-3 have relatively low reversible cycle stability.

[0107] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. In particular, it should be noted that any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention for those skilled in the art.

Claims

1. A method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate, characterized in that, Includes the following steps: (1) Dissolve the lithium iron phosphate battery material in a mixed aqueous solution containing organic acid and strong oxide, and filter after leaching reaction to obtain lithium-rich manganese solution and iron phosphate slag. (2) Add ammonia and manganese salt to the lithium-rich manganese solution to regulate the metal concentration; (3) Add surfactant and oxide to the regulated solution to carry out oxidation precipitation reaction, and obtain pre-lithium-doped surface-modified manganese tetroxide after filtration and washing; In step (1), the organic acid is at least one of citric acid, malonic acid, and phenylacetic acid; the molar ratio of the organic acid to the strong oxide is (0.4-0.8):1, and the solid-liquid ratio in the leaching reaction is 4-12 mL / g; In step (2), the concentration of Mn metal in the solution after adjustment is 0.2-2.2 mol / L.

2. The method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate as described in claim 1, characterized in that, In step (1), at least one of the following a)-b) is satisfied: a) The strong oxidizing agent is persulfate, ozone, oxygen, sodium hypochlorite, hydrogen peroxide, or chlorine; b) The molar ratio of the strong oxide to lithium manganese iron phosphate in the lithium manganese iron phosphate battery material is (0.5-1.2):

1.

3. The method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate as described in claim 1, characterized in that, In step (1), at least one of the following a)-c) is satisfied: a) Leaching reaction temperature: 60-90℃; b) Leaching reaction time: 4-10 hours; c) The stirring rate for the leaching reaction is 200-450 rpm.

4. The method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate as described in claim 1, characterized in that, In step (2), at least one of the following a)-c) is satisfied: a) The ammonia is at least one of ammonia water, ammonium chloride, ammonium sulfate, sodium 4-hydroxybenzenesulfonate, hydroxyacetamide, N-benzoyl-N-phenylhydroxylamine, ethylenediamine, and triethylamine; b) The manganese salt is at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, manganese acetate, and manganese phosphate; c) The amount of ammonia added is 3-12% of the molar amount of Mn metal.

5. The method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate as described in claim 1, characterized in that, In step (3), at least one of the following a)-d) is satisfied: a) The surfactant is at least one of the following: pyrrolidone, polyvinylpyrrolidone, 1-vinyl-2-pyrrolidone, 5-methyl-2-pyrrolidone, 2-pyrrolidone-5-carboxylic acid, sodium 4-hydroxybenzenesulfonate, sodium 3-carboxybenzenesulfonate, sodium 3-aminobenzenesulfonate, sodium 4-vinylbenzenesulfonate, sodium 4-ethylbenzenesulfonate, sodium lignin sulfonate, sodium aminosulfonate, and sodium benzoyl thioethane sulfonate; b) The oxide is air, ozone, oxygen, persulfate, chlorine, or sodium hypochlorite; c) The molar ratio of the surfactant to Mn metal in the solution is (0.005-0.05):1; d) The molar ratio of the oxide to the Mn metal in the solution is (0.7-1.1):

1.

6. The method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate as described in claim 1, characterized in that, In step (3), at least one of the following a)-d) is satisfied: a) The oxidation precipitation reaction temperature is 70-95℃; b) The stirring speed for the oxidation precipitation reaction is 300-500 rpm; c) The pH value for the oxidation precipitation reaction is 8-10; d) The oxidation precipitation reaction time is 10-20 h.

7. The method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate as described in claim 1, characterized in that, In step (1), the phosphate slag is dissolved in 1-3 mol / L sulfuric acid with a solid-liquid ratio of 3-8 mL / g. After filtration, phosphate seed crystals with an iron ion concentration of 10-25% are added to the solution, resulting in a seed crystal concentration of 50-80 g / L and a D50 of 0.1-2.4 μm. The solution is aged for 4-10 h, filtered, washed, and dried, and then calcined at 500-800 °C to obtain battery-grade phosphate.

8. A method for preparing pre-lithium-doped modified manganese tetroxide from lithium manganese iron phosphate as described in any one of claims 1-7.

9. The pre-lithium-doped modified manganese tetroxide as described in claim 8, characterized in that, The pre-lithium-doped modified manganese tetroxide contains 68 wt%-75 wt% Mn, 0.8 wt%-1.8 wt% Li and 0.4 wt%-3.2 wt% C, with a D50 of 10-15 μm.

10. A lithium manganese oxide battery material, characterized in that, It is prepared by using the pre-lithium-doped modified manganese tetroxide as described in claim 8 or 9.

Citation Information

Patent Citations

  • Preparation method for spherical doped lithium manganate

    CN107240692A

  • Method for recovering valuable elements from lithium manganese iron phosphate positive electrode waste

    CN115535987A

  • Method for preparing battery-grade anhydrous iron phosphate from iron phosphate waste residues after lithium extraction and battery-grade anhydrous iron phosphate

    CN116161636A